Critical Role of Transient Activity of MT1-MMP for ECM Degradation in Invadopodia - Watanabe, Ayako; Hosino, Daisuke; Koshikawa, Naohiko; Seiki, Motoharu; Suzuki, Takashi; Ichikawa, Kazuhisa (PLOS Computational Biology, 2013)
Author Summary Metastasis is the major cause of death in cancer patients. If metastasis is blocked, the survival rate will be greatly increased. Cancer cells are surrounded by ECM (extracellular matrix), which prevents their free movement. MT1-MMP is a potent membrane proteinase that degrades ECM, which is the first step of cancer cell invasion. Thus, the control of MT1-MMP activity is a key to the prevention of metastasis. Here we found a sharp transient peak in the ECM-degrading activity of MT1-MMP by computer simulations, and computational elimination of this peak greatly prolonged the ECM degradation. MT1-MMP is transported intracellularly to the surface of the membrane of cancer cells, and its insertion into the membrane is thought to occur in a pulsatile manner. Therefore, we asked whether the ECM-degrading efficacy was the same in low-frequency/high-concentration and high-frequency/low-concentration insertions of MT1-MMP. Unexpectedly, the low-frequency/high-concentration regimen resulted in much faster ECM degradation even if the time-averaged amount of MT1-MMP insertion was the same. Thus, reduction of the sharp transient activity and vesicular content of MT1-MMP are important therapeutic targets.